2010
DOI: 10.1038/npp.2010.26
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A1 Receptors and Microglial Cells Mediate CX3CL1-Induced Protection of Hippocampal Neurons Against Glu-Induced Death

Abstract: Fractalkine/CX3CL1 is a neuron-associated chemokine, which modulates microglia-induced neurotoxicity activating the specific and unique receptor CX3CR1. CX3CL1/CX3CR1 interaction modulates the release of cytokines from microglia, reducing the level of tumor necrosis factor-a, interleukin-1-b, and nitric oxide and induces the production of neurotrophic substances, both in vivo and in vitro. We have recently shown that blocking adenosine A 1 receptors (A 1 R) with the specific antagonist 1,3-dipropyl-8-cyclopent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
110
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(114 citation statements)
references
References 63 publications
4
110
0
Order By: Relevance
“…We decided to investigate the possible role of CXCL16 in protecting neurons from cell death following Glu-excitotoxic insult (100 M, 30 min). In this experimental condition Glu induces specific neuronal cell death without affecting glial cells (Chen et al, 2000;Lauro et al, 2010). When CXCL16 was administrated during Glu challenge, neuronal cell death was reduced in a concentrationdependent way, as shown in Figure 3A (n ϭ 5-9; p Ͻ 0.05).…”
Section: Cxcl16 Protects Hippocampal Neurons From Excitotoxic Cell Deathmentioning
confidence: 74%
See 3 more Smart Citations
“…We decided to investigate the possible role of CXCL16 in protecting neurons from cell death following Glu-excitotoxic insult (100 M, 30 min). In this experimental condition Glu induces specific neuronal cell death without affecting glial cells (Chen et al, 2000;Lauro et al, 2010). When CXCL16 was administrated during Glu challenge, neuronal cell death was reduced in a concentrationdependent way, as shown in Figure 3A (n ϭ 5-9; p Ͻ 0.05).…”
Section: Cxcl16 Protects Hippocampal Neurons From Excitotoxic Cell Deathmentioning
confidence: 74%
“…was removed and stored for later usage; neurons were washed and stimulated with Glu (100 M, 30 min) in modified Locke's buffer (without MgCl 2 plus 1 M glycine to stimulate all types of Glu receptors) in the presence or in the absence of CXCL16, hCX 3 CL1, or hCCL2 (100 nM) (Peprotech). Under these experimental conditions, only neurons die (Chen et al, 2000;Lauro et al, 2010). After treatment, cells were reincubated in the original c.m.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One particularly lucid series of experiments showed that neuronal fractalkine elicited adenosine release from microglia, activating survival pathways in excitotoxicity-challenged neurons via adenosine A1 receptors (Lauro et al 2008(Lauro et al , 2010. Initial findings in vitro were extended in vivo to a permanent focal ischemia model (Cipriani et al 2011) and were enriched by showing that fractalkine signaling also supported glutamate uptake by astrocytes (Catalano et al 2013).…”
Section: Fractalkine/receptor In the Nervous Systemmentioning
confidence: 95%